دور مــجـلـــس الدولــــة الجزائري فـي تكــــريـــــس دولـــــــة القـانـــون - حمادي, عائشة (جامعة الوادي -University eloued, 2022)
تبني التعديل الدستوري لسنة 1996 صراحة ولأول مرة الازدواجية القضائية بموجب المادة 152 منه التي نصت على إنشاء مجلس الدولة كهيئة مقومة لأعمال الجهات القضائية الإدارية، ولم يكتف المؤسس الدستوري بالدور القضائي لمجلس الدولة بل أضاف له الدور الاستشاري الذي يساهم بشكل فعال في إعداد النصوص القانونية سواء تعلق الأمر بمشاريع القوانين أو مشاريع الأوامر وتم التأكيد على هذا الدور الاستشاري بموجب القانون رقم 16-01 المؤرخ في 6مارس 2016 المعدل والمتمم للقانون 01-98 المتعلق باختصاصات المجلس الدولة وتنظيمه وسيره والقانون 18-02 المؤرخ في 4 مارس 2018 المتضمن التعديل. وعليه تكمن أهمية الوظيفة الاستشارية في المساهمة في إثراء وتطوير القواعد القانونية، كما تعتبر إجراء ضروريا لابد منه لنجاح وفعالية النشاط الإداري، إلا أن الوظيفة الاستشارية لمجلس الدولة الجزائري هي وظيفة محدودة، تقتصر على الاستشارة الإلزامية في مجال مشاريع القوانين والأوامر، ولا تمتد إلى مشاريع اقتراحات القوانين والتنظيمات، غير أن الإلزام يبقى فقط في طلب الرأي دون الإلزام بالأخذ به، كما أن مجلس الدولة يستشار في المجال التشريعي دون الإداري وهذا التصنيف لا يتفق مع ما هو معمول به في الأنظمة المقارنة. The constitutional amendment of 1996 explicitly adopted for the first time judicial duplication under Article 152 of it, which stipulated the establishment of the State Council as a regulating body for the work of the administrative judicial authorities. Ordering draft laws or draft orders This advisory role was confirmed by Law No. 16-01 of March 6, 2016, amending and supplementing Law 98-01 relating to the competences, organization and functioning of the State Council and Law 18-02 of March 4, 2018 containing the amendment. Accordingly, the importance of the advisory function lies in contributing to the enrichment and development of legal rules. It is also considered a necessary measure necessary for the success and effectiveness of administrative activity, but the advisory function of the Algerian State Council is a limited function, limited to mandatory consultation in the field of draft laws and orders, and does not extend to draft laws and regulations proposals, but the obligation remains only in seeking opinion without It is obligatory to adopt it, and the State Council is consulted in the legislative field rather than the administrative field, and this classification is inconsistent with what is applied in comparative systems.
ماستر اداري
Keywords: دور، مــجـلـــس الدولــــة ، الجزائري ، تكــــريـــــس، دولـــــــة القـانـــون; Role, Council of State, Algerian, Consecration, Rule of Law